Molecular screening of antibiotic-resistant determinants among multidrug-resistant clinical isolates of proteus mirabilis from SouthWest Nigeria (2017)
Background: Globally, and particularly in developing countries, the menace of anti-microbial resistance is an accelerating problem. In Nigeria, increase in bacterial resistance has been phenotypically established but due to high cost, few molecular studies have been reported. Objectives: This study screened for presence of transferable resistance genes and mobile genetic elements (MGEs) such as integron among multi-drug resistant (MDR) P. mirabilis. Methods: A total of 108 P. mirabilis strains collected from five tertiary hospitals in SouthWest Nigeria were subjected to antibiotic susceptibility study using disc-diffusion method. Transferable resistance genes and MGEs were amplified using Polymerase chain reaction (PCR) analysis and amplicons sequenced. Results: Varied resistance was observed against all the antibiotics tested. About 56% of the isolates were MDR including those from 0-12 years old children. PCR analysis revealed the presence of aac(6’)-Ib (33.3%), plasmid mediated quinolone resistance (PMQR) genes [qnrA (36.7%), acc(6’)-Ib-cr (5%)], TEM (48.3%), CTX-M (6.7%) and integrons class 1 (58.3%) and class 2 (26.7%). Sequencing analysis revealed blaTEM-1, blaCTX-M-15 associated with ISEcp1 and eight different arrays of gene cassettes: aadA1, aadA1-qacH, aadB-aadA2, aadA5, dfrA7, dfrA15, dfrA17, dfrA17-aadA5. Conclusion: Transferable resistance genes in association with MGEs are present in Nigerian P. mirabilis thus their potential in disseminating resistance.